Assessing the genetic diversity and characterizing genomic regions conferring Tan Spot resistance in cultivated rye - Sidhu, Jagdeep Singh; Ramakrishnan, Sai Mukund; Ali, Shaukat; Bernardo, Amy; Bai, Guihua; Abdullah, Sidrat; Ayana, Girma; Sehgal, Sunish K. (PloS one, 2019)
Rye (Secale cereale L.) is known for its wide adaptation due to its ability to tolerate harsh environments in semiarid areas. To assess the diversity in rye we genotyped a panel of 178 geographically diverse accessions of four Secale sp. from U.S. National Small Grains Collection using 4,037 high-quality SNPs (single nucleotide polymorphisms) developed by genotyping-by-sequencing (GBS). PCA and STRUCTURE analysis revealed three major clusters that separate S. cereale L. from S. strictum and S. sylvestre, however, genetic clusters did not correlate with geographic origins and growth habit (spring/winter). The panel was evaluated for response to Pyrenophora tritici-repentis race 5 (PTR race 5) and nearly 59% accessions showed resistance or moderate resistance. Genome-wide association study (GWAS) was performed on S. cereale subsp. cereale using the 4,037 high-quality SNPs. Two QTLs (QTs.sdsu-5R and QTs.sdsu-2R) on chromosomes 5R and 2R were identified conferring resistance to PTR race 5 (p < 0.001) that explained 13.1% and 11.6% of the phenotypic variation, respectively. Comparative analysis showed a high degree of synteny between rye and wheat with known rearrangements as expected. QTs.sdsu-2R was mapped in the genomic region corresponding to wheat chromosome group 2 and QTs.sdsu-5R was mapped to a small terminal region on chromosome 4BL. Based on the genetic diversity, a set of 32 accessions was identified to represents more than 99% of the allelic diversity with polymorphic information content (PIC) of 0.25. This set can be utilized for genetic characterization of useful traits and genetic improvement of rye, triticale, and wheat.